The case of eculizumab: litigation and purchases by the Brazilian Ministry of Health - Rosângela Caetano; Paulo Henrique Almeida Rodrigues; Marilena C Villela Corrêa; Pedro Villardi; Claudia Garcia Serpa Osorio- (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVES This study examined the purchases of eculizumab, a high-cost monoclonal antibody used in the treatment of rare diseases by Brazilian federal agencies, in terms of purchased quantities, expenditures, and prices. METHODS Eculizumab purchases made between March 2007 and December 2018 were analyzed, using secondary data extracted from the Federal Government Purchasing System (SIASG in Portuguese). The following aspects were assessed: number of purchases, purchased quantities, number of daily doses defined per 1,000 inhabitants per year, annual expenditures, and prices. The prices were adjusted by the National Broad Consumer Price Index for December 2018. Linear regression was used for trend analysis. RESULTS All acquisitions by federal agencies were made by the Brazilian Ministry of Health. The purchases began in 2009 with tender waiver to comply with legal demand. There was an increasing trend in the number of purchases and quantities acquired over time. Two hundred and eighty-three purchases were made, totaling 116,792 units purchased, 28.2% of them in 2018. The adjusted total expenses summed more than R$ 2.44 billion. After market approval by the Brazilian Health Regulatory Agency, the weighted average price fell approximately 35%, to values under the Medicines Market Chamber of Regulation established prices. CONCLUSION Eculizumab represented extremely significant expenditures for the Brazilian Ministry of Health during the period. All purchases were made to meet demands from lawsuits, outside the competitive environment. The market approval of eculizumab promoted an important price reduction. This study indicates the relevance of licensing and the need for permanent monitoring and auditing of drug purchases to meet legal demands.